NEEDS ASSESSMENT DALAM RANGKA PROGRAM PEMBERDAYAAN UMKM KULIT DI DAERAH ISTIMEWA YOGYAKARTA - Rofiatun Nafiah (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2013)
This research tends to give an overview on needs assessment done by government institutions in order to determine the empowerment programs for leather Small and Medium enterprises (Leather-SMEs) in Yogyakarta. This research uses interview, questionnaires, direct observations and documentation techniques to gain the data; and employs descriptive method to analyze the data. Results of the research show that before designing the empowerment programs for leather SMEs, the institutions have not optimally done needs assessment, and even without any needs assessment at all. Furthermore, further research needs to be conducted in order to determine appropriate methods and steps in the implementation of needs assessment.